PENINGKATAN KECERDASAN KINESTETIK MELALUI PERMAINAN GAMES BALL PADA ANAK USIA 4-5 TAHUN DI RA DAARUL MUTTAQIN BANTUR-MALANG - Rohmania, Ari; Rohmawati, Afifatu (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
Games are one of the easy-to-apply learning techniques such as ball games. This game applies six techniques in early childhood kinesthetic learning. The purpose of this study was to describe the form and results of kinesthetic learning through ball games in children aged 4-5 years. The research methodology used is